I. B. M. Colossus in tranistion - "Sobel , Robert" (Toronto, 1983)
Sixty years ago it was a small manufacturer of cheese slicers and adding machines. Today it's a powerful super corporation at the leading edge of the electronics revolution. Now noted business authority and writer Robert Sobel penetrates the publicity-shy fortress of IBM to explode the myths and set the record straight
Keywords: International business machine corporation